A National Study of the Validity and Utility of the Comprehensive Assessment of School Environment (CASE) Survey. (June 2016) - McGuffey, Amy R.
A healthy school climate is necessary for improvement. The purpose of this study was to evaluate the construct validity and usability of the Comprehensive Assessment of School Environment (CASE) as it was purportedly realigned to the three dimensions of the Breaking Ranks Framework developed by the National Association of Secondary School Principals. Over 4, 000 stakeholders representing 28 secondary schools across 21 states participated. A four-factor solution was derived and CASE was found to be usable.